2013
DOI: 10.1128/aac.00179-13
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of Colistin plus Rifampin against Colistin-Resistant KPC-Producing Klebsiella pneumoniae

Abstract: f Infections caused by carbapenem-resistant KPC-producing Klebsiella pneumoniae are responsible for high rates of mortality and represent a major therapeutic challenge, especially when the isolates are also resistant to colistin. We used the checkerboard method to evaluate the synergistic activity of 10 antibiotic combinations against 13 colistin-resistant KPC-producing K. pneumoniae isolates (colistin MIC range of 8 to 128 mg/liter). Colistin plus rifampin was the only combination that demonstrated consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 21 publications
3
78
0
3
Order By: Relevance
“…Case series have been documented from Italy, the United States, Hungary, and Greece. [4][5][6][7][8][9][10] However, such reports are rare, although we suspect underreporting of cases. One of the challenges faced in the developing world is lack of isolation facilities in adequate numbers and the lack of adequate awareness, which makes infection control a priority.…”
Section: Colistin-resistant Klebsiella Pneumoniae : Report Of a Clustmentioning
confidence: 90%
“…Case series have been documented from Italy, the United States, Hungary, and Greece. [4][5][6][7][8][9][10] However, such reports are rare, although we suspect underreporting of cases. One of the challenges faced in the developing world is lack of isolation facilities in adequate numbers and the lack of adequate awareness, which makes infection control a priority.…”
Section: Colistin-resistant Klebsiella Pneumoniae : Report Of a Clustmentioning
confidence: 90%
“…We are now in a state to prohibit the emergence of future resistance and are made workable with the ease of combination therapy using different classes of antibiotics for the betterment in efficacy (13). In addition, it is necessary to have knowledge in selecting antibiotics with appropriate synergistic activity (14). Combination of colistin with carbapenem is studied in detail to at least save the last resort of available antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, AMK and COL demonstrated synergy, but exclusively against COL-resistant CR-Kp strains. Previous studies among COL-resistant CR-Kp strains identified combinations of COL plus rifampin (19,20) or doxycycline (19) as potentially synergistic. These combinations may be more attractive for subsequent studies given the potential additive toxicities of AMK and COL combination therapy.…”
mentioning
confidence: 99%